Strategi Komunikasi Politik dalam Pemenangan Pemilihan Kepala Daerah Kabupaten Belu Tahun 2024 : (Studi pada Pemenangan Willy Lay-Vicente Hornai Pasangan Calon Bupati dan Wakil Bupati Kabupaten Belu) - Selviana Kini Fahik; Ananias R.P. Jacob; Philps Y.N. Ndoda; Rex Tiran (Lembaga Pengembangan Kinerja Dosen, 2025)
This study aims to determine and describe the political communication strategy through the Political Marketing strategy in Winning the 2024 Belu Regency Regional Head Election in the Winning of Willy Lay-Vicente Hornai, the Pair of Regent and Deputy Regent of Belu Regency. This study uses a descriptive approach with a qualitative method, and utilizes the theory of political marketing strategy. The data collection techniques used are observation, interviews, and documentation. The data analysis technique uses three stages, namely data reduction, data presentation, and verification/drawing conclusions. The results of the study show that the political marketing approach carried out by the Winning of the 2024 Belu Regency Regional Head Election in the Winning of Willy Lay-Vicente Hornai, the Pair of Regent and Deputy Regent of Belu Regency, succeeded in winning the election with a valid vote of 46,173 votes in the 2024 Belu Regency regional head election. The two main methods used are direct and indirect approaches. The direct approach includes face-to-face interactions such as door-to-door campaigns and participation in social activities. The social activities are carried out in the form of political education campaigns and economic and social empowerment programs in rural areas, including farmer programs, cooperatives, and micro, small and medium enterprises. This direct approach has proven to have a significant positive impact in reaching various levels of society. Meanwhile, the indirect approach utilizes social media to disseminate information related to campaign activities and regional head candidates. This helps build a positive image of the Regent pair and expands the reach of political messages.